2014
DOI: 10.1590/s1516-8913201402370
|View full text |Cite
|
Sign up to set email alerts
|

Current status of rodenticide intoxication in Brazil: a preliminary survey from 2009 to 2011

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…Analyzing temporal trends of occurrences, in the fourth biennial (2012-2013) most poisonings by chumbinho were reported, corroborating epidemiological trend study data that showed an increase of 60.0% of case reporting for this agent in Brazil in the period of 2009 and 2011 and concluded that there was "epidemic outbreak" of toxicological event (4) .…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Analyzing temporal trends of occurrences, in the fourth biennial (2012-2013) most poisonings by chumbinho were reported, corroborating epidemiological trend study data that showed an increase of 60.0% of case reporting for this agent in Brazil in the period of 2009 and 2011 and concluded that there was "epidemic outbreak" of toxicological event (4) .…”
Section: Discussionsupporting
confidence: 72%
“…The largest number of cases involving adults relates to the number of suicide attempts/suicide with the use of the product, considered one of the means for expanding these intentional acts (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) . The suicide attempt by chumbinho is considered an important cause of morbidity and mortality in Brazil and indicated by the World Health Organization as an increasing public health problem (12)(13) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O local, o período e as características das notificações foram delimitadas com filtros disponíveis, conforme mencionado. O procedimento de coleta de dados foi semelhante ao relatado em outros estudos, como Papini e Nakagawa (2014) 18 Para avaliar a quantidade anual de notificações de intoxicações exógenas por raticidas ao longo dos últimos 15 anos, os valores foram normalizados a cada um milhão de residentes no Brasil (notificações/1.000.000), levando em consideração as projeções intercensitárias do Instituto Brasileiro de Geografia e Estatística (IBGE), também disponibilizadas pela ferramenta TabNet. Para avaliar o impacto do surto de SARS-CoV-2 e a pandemia de COVID-19, a quantidade anual foi estratificada mensalmente, considerando três grupos: (1) pré-pandemia/controle (abril de 2019 até março de 2020), (2) primeiro ano (abril de 2020 até março de 2021) e (3) segundo ano (abril de 2021 até março de 2022) (n = 12/grupo).…”
Section: Métodosunclassified